Are Assessment Exemplars Perceived to Support Self-Regulated Learning in Teacher Education? - Grainger, Peter R.; Heck, Deborah; Carey, Michael D. (Frontiers in Education, 2018)
Assessment exemplars are a tool to guide students to what is valued by assessors in a specific assessment task, in short, as examples which illustrate, typically, dimensions of quality. Often high-quality exemplars are provided in formative assessment contexts to develop self-regulated learning. We were interested in researching the perceived efficacy and impact of a variety of assessment exemplars, ranging from low to high quality, in teacher education courses at a regional university. More specifically, this research explores student perceptions of how assessment exemplars support the development of phases and signposts for self-regulated learning. We surveyed 72 students and found that students accessed exemplars regularly and found them useful in providing detailed guidance that went beyond the descriptions of assessment tasks found in course outlines and assessment rubrics. They valued various types of exemplars, a range of quality, and the inclusion of annotated and unannotated versions of exemplars. We identified four key themes from the analysis: assessment exemplars as guides, supplements, starting points, and standards for comparison. Our results support the provision of exemplars as a tool to build student self-regulation in three phases and their contribution to the four signposts on the path from social to independent self-regulatory practice (Zimmerman and Kitsantas, 2014).